Examining the Psychosis Continuum - DeRosse, Pamela (Curr Behav Neurosci Rep, 2015)
The notion that psychosis may exist on a continuum with normal experience has been proposed in multiple forms throughout the history of psychiatry. However, in recent years there has been an exponential increase in efforts aimed at elucidating what has been termed the ‘psychosis continuum’. The present review seeks to summarize some of the more basic characteristics of this continuum and to present some of the recent findings that provide support for its validity. While there is still considerable work to be done, the emerging data holds considerable promise for advancing our understanding of both risk and resilience to psychiatric disorders characterized by psychosis.